The regulatory effects of bioactive polysaccharides on intestinal function and bile acids: chemical structures, bioactivities, and mechanisms - Wang, Anqi; Xiong, Wugui; Li, Jing; Hu, Yingfan; Zou, Liang; Liu, Ying (Frontiers in Nutrition, 2024)
Polysaccharides are one of the important components of the human diet, offering a wide range of biological activities, especially in improving inflammation in the digestive system and addressing metabolic diseases. Among all the reported bioactivities of polysaccharides, their regulation effects on intestinal function and bile acids (BAs) are gradually attracting the attention of more researchers. Bile acids, the main components of intestinal lipid digestive fluid, are also key signal factors for metabolic homeostasis and impact overall health. Polysaccharides usually interact directly or indirectly with the gut and gut microbiota to participate in the regulation process of reabsorption, metabolism, and excretion of bile acids in humans, thereby exerting their role in the intervention of human diseases. In this review, we comprehensively reviewed the effects of bioactive polysaccharides on the regulation of intestinal function and bile acids. The chemical structures, bioactivities, and potential mechanisms for their activities were also reviewed. This study aimed to provide a comprehensive reference for future research on the activities and mechanisms of polysaccharides, as well as to offer important strategies and insights for the development of bioactive polysaccharides to prevent inflammatory and metabolic diseases.